2018
DOI: 10.1155/2018/2315938
|View full text |Cite
|
Sign up to set email alerts
|

Combining and Using the Utrecht Method and the Analytic Hierarchy Process to Facilitate Professional and Ethical Deliberation and Decision Making in Complementary and Alternative Medicine: A Case Study among a Panel of Stakeholders

Abstract: Background In daily practice, healthcare practitioners face many challenges in ethical and professional decision making. Currently, little is known on the ethical and professional deliberations and weighing benefits against risks in daily complementary and alternative medicine (CAM) practice. The aim of this study was to combine the Utrecht method and the Analytic Hierarchy Process (AHP) in deliberations, weighing benefits against risks of using ginger for a pregnant woman suffering nausea and vomiting of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In this study, we used the Delphi technique to develop and achieve consensus on a definition of MTEs and scenarios that represent different MTE situations. The Delphi technique was extensively used in developing and achieving consensus on inconclusive issues in healthcare [8, 9, 2027]. Moreover, this technique was used in developing and achieving consensus on other forms of medication errors [8, 9, 16, 17].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the Delphi technique to develop and achieve consensus on a definition of MTEs and scenarios that represent different MTE situations. The Delphi technique was extensively used in developing and achieving consensus on inconclusive issues in healthcare [8, 9, 2027]. Moreover, this technique was used in developing and achieving consensus on other forms of medication errors [8, 9, 16, 17].…”
Section: Methodsmentioning
confidence: 99%
“…Patients in Palestine receive healthcare services from three main providers: (1) governmental sector, (2) private sector, and (3) international and nongovernmental organizations like the United Nations Relief and Works Agency for Palestine Refugees (UNRWA) [ 36 ]. In addition to conventional Western medicine, many Palestinians turn to the different modalities of CAM [ 7 , 8 , 10 13 , 28 ]. These CAM modalities are either used to complement or as alternatives to conventional Wester medicines.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to industry and community pharmacy practice, the pharmacy graduates are trained to assume all roles in healthcare facilities including primary, secondary, and tertiary healthcare facilities. Pharmacists are the main providers of CAM [ 8 , 11 ]. As recent studies have reported a worldwide increase in using CAM modalities among hospitalized patients [ 14 , 15 ], like their peers elsewhere, pharmacists in Palestine are expected to deliver a variety of pharmaceutical care services to patients using such modalities, particularly, those admitted to healthcare facilities that employ integrative medicine paradigm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The Analytic Hierarchy Process is a powerful tool that has been extensively used in multi-criteria decision analysis, notably, in healthcare [8385]. The Analytic Hierarchy Process allows addressing and facilitating making decisions on complex problems with multi-criteria.…”
Section: Methodsmentioning
confidence: 99%